Stepovers and Signal Detection: Response Sensitivity and Bias in the Differentiation of Genuine and Deceptive Football Actions - Jackson, Robin C.; Barton, Hayley; Ashford, Kelly J.; Abernethy, Bruce (Frontiers in Psychology, 2018)
The ability to differentiate genuine and deceptive actions was examined using a combination of spatial and temporal occlusion to examine sensitivity to lower body, upper body, and full body sources of visual information. High-skilled (n = 24) and low-skilled (n = 24) association football players judged action outcome as the player either took the ball in one direction (genuine action) or attempted to deceive the observer by stepping over the ball and going in the other direction. Signal detection analysis was used to calculate measures of sensitivity (d’) in differentiating genuine and deceptive actions and bias (c) toward judging an action to be genuine or deceptive. Analysis revealed that high-skilled players had higher sensitivity than low-skilled players and this was consistent across all spatial occlusion conditions. Low-skilled players were more biased towards judging actions to be genuine. Receiver Operating Characteristic (ROC) curves revealed that accuracy on deceptive trials in the lower body and full body conditions best predicted group membership. The results highlight the value of using signal detection analysis in studies of deceptive actions. They suggest that information from the lower body or upper body was sufficient for differentiating genuine and deceptive actions and that global information concurrently derived from these sources was not necessary to support the expert advantage.